Findings on the effects of combining lump sum cash transfers with technical and farm management advice to increase productivity and link farmers to value chains - CGIAR Research Program on Policies, Institutions, and Markets (2018)
Results are being disseminated to attempt to find funding to take this innovation to the next level.